The good public administration in the XXI century: Analysis of the Colombian case (2018)
The article aims to identify the meaning of the concept of good Public Administration in the 21st century and its impact on Administrative Law, with emphasis on the Colombian case. The paper makes some precisions on the origins of Administrative Law in the liberal State, to then contrast these characteristics with Administrative Law and good Public Administration in the constitutional and democratic rule of law of the 21st century. It makes a presentation of the legal content of the fundamental right to a good Public Administration and its main characteristics in accordance with the scholarship and the main legal documents dealing with the subject, such as the Ibero-American Charter of the Rights and Duties of the Citizen in relation to Public Administration of 2013 and the European Charter of Fundamental Rights of 2000. Finally, the article describes how this new concept is applied in Colombia, reporting some experiences adopted in that country with the aim of improving the quality of public management. © 2018 Editora Dom Helder. All rights reserved.